Mechanical properties of diamond–TiB2 composites - Szutkowska, M.; Rozmus, M.; Figiel, P.; Jaworska, L. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2012)
The presented paper characterizes the basic mechanical and physical properties of sintered diamond-titanium diboride (submicro) and diamond-titanium diboride (nano) composites. The effect of reduction of powder size from the submicron scale to the nano scale of the ceramic bonding phase (TiB₂) in diamond composites on selected mechanical properties (Young’s modulus, Vickers hardness, fracture toughness, coefficient of friction) has been reported. Composites were prepared from initial powders of diamond (MDA36, Element Six) with addition of 10 mass % submicron TiB₂ (H.C. Starck F) and 10 mass % nanopowder TiB₂ (American Elements). Compacts were sintered at pressure 8±0,5 GPa and 2233±50 K using the high pressure-high temperature Bridgman type apparatus. These investigations allow the possibility of using this materials to be enhacced as ceramic tool materials, in particular as burnishing tools.